In Search of Better Ways to Develop Solar Markets : The Case of Comorros - World Bank (Washington, DC, 2014)
This document reports the results of an ESMAP project in Comoros that was carried out between summer 1997 and September 1999 and funded by the French Ministry of Cooperation. It also is a discussion paper exploring alternative ways to promote solar electricity. The project was meant to develop the market for solar electricity and to help non-electrified households attain higher comfort levels without waiting for the electricity company to expand its distribution network. The outcome of the project showed that large projects were not necessary to begin developing the market for solar equipment.